2017
DOI: 10.1101/232058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular map of GNAO1-related disease phenotypes and reactions to therapy

Abstract: The GNAO1 gene codes for the most commonly expressed Gα protein in the central nervous system. De novo GNAO1 variants cause complex early-onset neurological phenotypes, sometimes with distinct epilepsy or movement disorder manifestations, and sometimes with both manifestations in the same patient. G-protein coupled receptor (GPCR) signaling is among the best studied molecular interaction pathways in the human organism, which provides the input needed to quantitatively evaluate how mutations modify the GPCR sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Finally, we found that loss of Gαo in iMSNs was responsible for inducing dystonia-like features often observed GNAO1 patients ( Mihalek et al, 2017 ), which could be considered a part of hyperkinetic motor program constrained by this neuronal population ( Durieux et al, 2009 ). The selective involvement of Gαo supports a dominant role of iMSN circuitry in dystonia ( Berardelli et al, 1998 ), including observed alterations in electrophysiological properties of iMSNs in mouse models of dystonia ( Sciamanna et al, 2020 ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Finally, we found that loss of Gαo in iMSNs was responsible for inducing dystonia-like features often observed GNAO1 patients ( Mihalek et al, 2017 ), which could be considered a part of hyperkinetic motor program constrained by this neuronal population ( Durieux et al, 2009 ). The selective involvement of Gαo supports a dominant role of iMSN circuitry in dystonia ( Berardelli et al, 1998 ), including observed alterations in electrophysiological properties of iMSNs in mouse models of dystonia ( Sciamanna et al, 2020 ).…”
Section: Discussionmentioning
confidence: 71%
“…In light of the elucidated role of Gαo in regulating signaling to cAMP and motor coordination, we next investigated the impact of several mutations in Gαo associated with GNAO1 encephalopathy ( Kelly et al, 2019 ; Mihalek et al, 2017 ) using our recently developed molecular deconvolution platform ( Masuho et al, 2018 ). Structural modeling showed that these mutations mapped to highly conserved motifs among the Gα protein family residing predominantly around the phosphate-binding loop (P loop), switch II, and switch III regions ( Figure 4A ), suggesting potential influence on Gαo activation ( Bosch et al, 2012 ) and its interaction with guanine nucleotides ( Nakamura et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For GNAO1 encephalopathy, although tetrabenazine was demonstrated to be the most effective drug, emergency GPi-DBS was shown to be helpful for those patients with hyperkinetic exacerbations (9). Furthermore, dissection of phenotype-genotype correlation suggested that different GNAO1 mutations affect the G protein function for the signaling loop in distinct ways that implicated different treatment options (11). This suggested possible application of precision medicine for different GNAO1 variants identi ed in the patients.…”
Section: Potential Genotype-targeted Treatment Implicationsmentioning
confidence: 99%
“…Phenotypic diagnosis only has limitations as many symptoms may have more than one underlying etiology and any particular pathophysiology can result in a complex combination of symptoms (6). Genetic diagnosis allows a comprehensive understanding of the underlying pathophysiology and provides speci c treatment options (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%